Kozak w Brukseli, czyli Mariana Pankowskiego krytyczny zamysł na styku kultur - Jan Burnatowski (Postscriptum Polonistyczne)
The article attempts to reinterpret Marian Pankowski’s literary project. The author that has been marginally present in Polish reception, read once again in the context of modern theories and discourses reveals the maturity and timeliness of his themes, asking difficult questions concerning the identity of man in the 20th century. The author of Matuga is interested in the very foundations of premodern world; he asks questions about the sense of religion, meaning of the traditionally perceived concept of nationality and ‘functionality’ of preVictorian model of morality.